Pathomorphology of membranes appearing in proliferative vitreoretinopathies - Laudańska-Olszewska, Iwona; Omulecki, Wojciech; Dzięgielewski, Krzysztof; Pikulski, Zbigniew; Omulecka, Aleksandra (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Immunohistochemical techniques were used to investigate the cell content of epiretinal membranes occuring in proliferative vitreoretinopathy (PVR) and proliferative diabetic retinopathy (PDR). Ten epiretinal membranes were obtained during surgery from eyes with PVR and five from eyes with PDR. This material was studied histopathologically and immunohistochemically. Retinal pigment epithelial cells, glial cells, macrophages, T lymphocytes and type IV collagen were identified in these membranes. The findings indicate that the cells mentioned possess a potential role in creating vitreoretinal membranes in PVR and PDR.